Does Parenting Moderate the Association Between Parental and Offspring Offending? - Lee, Bomin (Journal of developmental and life-course criminology, 2025)
The purpose of this study is to examine the pathways of intergenerational transmission of convictions among 282 sons and their parents using longitudinal data from the Cambridge Study in Delinquent Development (CSDD), a prospective study conducted in South London. Logistic regression and moderation analyses revealed that fathers’ convictions significantly increase the likelihood of a son’s conviction, particularly when accompanied by negative parenting styles. Moreover, a positive maternal parenting style functions as a protective factor that mitigates the negative effects of the father’s convictions. In conclusion, parenting behaviors function not merely as mediators but as active moderators in the intergenerational transmission of convictions. This study underscores the need for family-centered preventive interventions that support fathers in adopting restorative parenting roles and recommends programs that enhance positive father-son interactions.